Serum eosinophilic cationic protein level and hematological parameters in infants with cow's milk protein allergy - Erkan Dogan; Eylem Sevinc (Indonesian Pediatric Society, 2019)
Background Various biomarkers have been investigated in the diagnosis of cow's milk protein allergy (CMPA) in infants. To our knowledge, no prior studies have evaluated serum eosinophil cationic protein (sECP), neutrophil-lymphocyte ratio (NLR), and mean platelet volume (MPV) concurrently in infants with CMPA. Objective To compare sECP levels, MPV, and NLR in infants with and without CMPA, as well as to investigate the suitability of these parameters as biomarkers in the diagnosis of CMPA. Methods Fifty-six children with CMPA were compared to 40 healthy, similar to distribution of age and sex normal infants as controls. The serum ECP levels were detected by a chemiluminescence assay. The MPV values were calculated by devices in hemogram parameters. The NLR values were obtained by dividing the neutrophil count by the lymphocyte count. Results The median sECP level in the CMPA group was significantly higher than in the control group (23.5 and 9.27 ng/mL, respectively; P=0.001). However, there were no significant differences between groups with regards to median MPV (8.5 and 8.6 fL, respectively; P=0.149) and median NLR (0.35 and 0.37 respectively; P=0.637). Correlation analysis of sECP level with MPV and NLR in the CMPA group revealed no significant relationships (P>0.05 for both). In the Receiver-operating characteristic (ROC) curve analysis, the optimal cut-off levels to identify CMPA for sECP, MPV, and NLR were 18.4 ng/mL (60.7% sensitivity, 97.5% specificity, and AUC: 0.831), 10.05 fL (54% sensitivity, 77.5% specificity, and AUC: 0.413) and 0.97 (14.3% sensitivity, 50% specificity, and AUC: 0.528), respectively. Conclusions The sECP level and blood eosinophil count are significantly higher in infants with CMPA, but MPV and NLR do not differ between infants with and without CMPA. There are also no significant correlations in the CMPA group between sECP and MPV, as well as sECP and NLR. Serum ECP might be useful as a potential biomarker for diagnosing CMPA.